Um Estudo sobre a Avaliação do Custo de Aplicação da Análise de Mutantes na Validação de Máquinas de Estados Finitos - Carvalho, Renata A. de; Fabbri, Sandra Camargo P. F.; Maldonado, José Carlos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1999: Anais do XIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1999.23930, 1999)
Finite State Machine (FSM) is one of the most used techniques for the specification of the Reactive Systems behavioral aspect, for instance, communication protocols. The validation of these specifications, in the case of protocols, conformance testing, is a relevant topic and the aim of many researches. A tendency to characterize an error model to conduct the validation activity is identified. Recently, the adequacy of the use of Mutation Analysis Criterion (MA), traditionaly used in program testing, has been studied in the context of FSM validation. This paper presents the results of an experiment that was conducted aiming at contributing to evaluate the application cost of Mutation Analysis and, in this direction, an essential mutant operators set for FSM is invetigated, aiming at the cost reduction without compromissing the quality of testing and validation activities. The results presented contribute for establishement of a knowledge body on the perspective of defining an incremental, low-cost testing and validation strategy in the context of FSM.